The Influence of Knee Phenotypes Based on Coronal Plane Alignment of the Knee on Intraoperative Soft Tissue Balance and Clinical Outcomes: Comparison between Kinematically and Mechanically Aligned Total Knee Arthroplasty - Tachibana, Shotaro; Matsumoto, Tomoyuki; Nakano, Naoki; Tsubosaka, Masanori; Kamenaga, Tomoyuki; Kuroda, Yuichi; Hayashi, Shinya; Kuroda, Ryosuke (The Journal of Knee Surgery, 2025)
This study examined the impact of preoperative coronal plane alignment of the knee (CPAK) classification on intraoperative soft tissue balance and postoperative clinical outcomes in patients undergoing modified kinematically aligned (mKA) and mechanically aligned (MA) total knee arthroplasty (TKA). A total of 90 knees treated with mKA-TKA and 63 knees treated with MA-TKA were classified based on CPAK. After adjusting for confounding factors, intraoperative soft tissue balance, including varus/valgus balance and joint component gap, range of motion (ROM), and the 2011 Knee Society score (KSS), were compared 1 year postoperatively using one-way ANOVA. The analysis included 69 knees classified as type I and 18 type II in the mKA group, and 52 type I and 11 type II in the MA group. Varus balance at 30 and 60 degrees flexion was significantly larger in mKA type I and MA type I compared to mKA type II (p < 0.001, 0.005, <0.001, 0.008). At 90 degrees, mKA type I showed a larger varus balance than both MA type I and mKA type II (p = 0.008, 0.002), while at 120 degrees, mKA type I demonstrated a larger varus balance than MA type I (p < 0.001). The improved ROM in mKA type I was greater than in MA type I (p = 0.04). Improvement in the objective indicator of the 2011 KSS was better in mKA type I than in mKA type II, and patient satisfaction was significantly better in mKA type I compared to both mKA type II and MA type I (p = 0.01, <0.001, 0.03). mKA type I preserved lateral laxity in mid- and deep flexion compared to both mKA type II and MA type I, potentially contributing to improved ROM and clinical outcomes.
Keywords: coronal plane alignment of the knee; total knee arthroplasty; kinematic alignment; mechanical alignment